How Does Indonesian Chronic Disease Patient Adhere to Their Treatment? A Cross-Sectional Analysis of 11,408 Subjects - Pradipta IS; Aprilio K; Ningsih YF; Pratama MAA; Gatera VA; Alfian SD; Iskandarsyah A; Abdulah R (Patient Preference and Adherence)
Ivan Surya Pradipta,1,2,* Kevin Aprilio,1,2,* Yozi Fiedya Ningsih,1,2 Mochammad Andhika Aji Pratama,2 Vesara Ardhe Gatera,3 Sofa Dewi Alfian,1,2 Aulia Iskandarsyah,4 Rizky Abdulah1,2 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 2Drug Utilization and Pharmacoepidemiology Research Group, Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 3Department of Pharmaceutical Biology, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 4Department of Clinical Psychology, Faculty of Psychology, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia*These authors contributed equally to this workCorrespondence: Ivan Surya Pradipta, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jalan Ir. Soekarno KM 21, Jatinangor, Sumedang, West Java, 45363, Indonesia, Email ivanpradipta@unpad.ac.idBackground: Chronic disease has become an increasing burden in Indonesia, increasing the importance of treatment adherence to control the disease prognosis. Therefore, we aim to determine the prevalence and characteristics of nonadherence in Indonesian chronic disease population.Methods: We identified 11,408 adult subjects with chronic diseases from the fifth Indonesian Family Life Survey. We defined treatment nonadherence as the outcome variable and characteristics related to the World Health Organization Multidimensional Adherence Model as exposure variables. We used descriptive and multivariable analyses to analyze factors related to treatment nonadherence.Results: We identified that 57% (95% CI 56.1– 57.9) of chronic disease patients were nonadherent to their treatment. Treatment nonadherence was notable in subjects with liver disease (61.8%), tuberculosis (59.8%), digestive diseases (57.9%), other lung diseases (56.8%), psychiatric diseases (51.6%), asthma (51.2%), and hypertension (50%). Treatment nonadherence was associated with socioeconomic-related factors of being aged 15– 65 years, living in rural areas, having history of formal education, and having a household size of 2– 6 people. Furthermore, in patient- and condition-related factors, positive perceptions of their health condition, missing 0– 7 days of their regular activity in the last month, being ex- and non-smokers, having no depression symptoms, and having only one chronic disease were associated with treatment nonadherence.Conclusion: Treatment nonadherence for chronic diseases in Indonesia was found to be prevalent. Further consideration of characteristics associated with treatment nonadherence should be given to ensure optimal control of chronic diseases.Keywords: chronic diseases, adherence, socioeconomic factors, patient-related factors, condition-related factors